E-Academic Supervision Models and Sustainable Teacher Professional Development: A Systematic Review with Implications for Junior High Schools - Helen Helen; Muhammad Kristiawan; Eko Risdianto (JPI: Jurnal Pustaka Indonesia, 2026)
This systematic review aims to identify and evaluate e-academic supervision models in junior high schools and analyze their contribution to sustainable teacher professional development (TPD). Following PRISMA 2020 guidelines, a comprehensive search of Scopus, Web of Science, ERIC, and Google Scholar was conducted for publications from 2023 to 2025. After screening, 21 peer-reviewed studies were analyzed using thematic synthesis. Four dominant models emerged: asynchronous video-based supervision, real-time virtual classroom observation, hybrid feedback systems, and cloud-based portfolio assessment. Results indicate that while these models positively influence teacher reflection and instructional improvement, their sustainability mechanisms such as continuous follow-up and data-driven goal setting remain underdeveloped. Unlike prior reviews focused on general e-supervision, this study offers novelty by specifically targeting junior high schools and proposing a sustainability framework that links e-supervision components to long-term TPD indicators. Practically, the synthesized models guide school supervisors and policymakers in designing or selecting e-supervision systems that foster continuous teacher development, especially in remote or resource-constrained settings. This review contributes the first comprehensive typology of e-supervision models for junior high contexts and advances educational technology and TPD literature through a conceptual sustainability matrix.